Exploring Adsorption Phenomena in Pharmaceutical Formulation Design: A Systematic Quality-By-Design Approach for Agomelatine-Loaded Liquisolid Compact Tablets - Thalluri, Chandrashekar (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: In our quest to maximize the therapeutic potential of Agomelatine, we embarked on a study wherein we formulated it into liquisolid compact tablets, strategically designed to enhance its dissolving performance and unlock its antidepressant efficacy. Materials and Methods: Employing the Quality by Design (QbD) methodology, specifically a randomized, non-block, central composite design with a response surface study type, quadratic model, and version 13.0.5.0, we meticulously developed nine alternative formulations (F1-F9). The non-volatile solvent, polyethylene glycol 400, played a pivotal role, with the non-volatile solvent loading factor (X1) and the excipient ratio of carrier to coating material (X2) serving as key independent variables. Evaluation of the formulations centered on two critical parameters: the angle of repose (Y1) and in-vitro percentage drug release (Y2). Employing Kawakita and Heckel’s methods, we discerned the dense nature of compact particles and their favorable compaction properties. The addition of Aerosil 200 alongside microcrystalline cellulose showcased improved compressibility through plastic deformation. Comprehensive pre- and post-compressional parameter assessments were established in Indian Pharmacopiea standard procedures. The release order kinetics were analyzed using DD solver as a statistical tool. Results: It pointed to the (F8) liquisolid formulation as particularly impactful, out shining other alternatives. Tablets were successfully fabricated using the direct compression method (F10). Our study extended to assess the similarity factor (f2) with a marketed sample (Agoprex 25 mg) and conducted stability studies for 90 days in line with ICH guidelines. Post 90 days, an analysis of variance demonstrated a P = 0.386, surpassing the threshold of P > 0.05, indicating negligible variation in in-vitro dissolution parameters. Conclusion: Our research underscores the effectiveness of liquisolid encapsulation as a distinctive strategy, significantly elevating the dissolving performance of Agomelatine and, consequently, enhancing its antidepressant efficacy. The application of QbD principles, coupled with a meticulous analysis of formulation variables and thorough tablet property evaluations, has yielded valuable insights, paving the way for an optimized liquisolid compact tablet formulation for agomelatine.